1991
DOI: 10.2135/cropsci1991.0011183x003100020027x
|View full text |Cite
|
Sign up to set email alerts
|

Grain Yield vs. Spike Number in Winter Wheat in a Humid Continental Climate

Abstract: Wheat (Triticum aestivum L.) yields often are closely related to spike number per unit ground area. This study was conducted to determine whether, for soft white winter wheat in a region with a humid continental climate, this relationship is determined primarily by changes in total dry weight accumulation (TDW), harvest index (HI), or both. The study involved several field experiments in which seeding density varied from 6 to 24 g m−2, sowing dates ranged from 14 September to 1 November, alternate rows were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…In case of seed priming more grains spike -1 (40.18) were produced by water soaked seeds and less number of grains spike -1 (39.33) were produced by dry sown seed. Our results are in line with the findings of [16,27] who reported that in mung bean grains pod -1 enhanced by treated seeds. who stated that seed priming increased grains weight and biomass.…”
Section: Spikes M -2supporting
confidence: 94%
“…In case of seed priming more grains spike -1 (40.18) were produced by water soaked seeds and less number of grains spike -1 (39.33) were produced by dry sown seed. Our results are in line with the findings of [16,27] who reported that in mung bean grains pod -1 enhanced by treated seeds. who stated that seed priming increased grains weight and biomass.…”
Section: Spikes M -2supporting
confidence: 94%